Editorial - Thorsen, Liv Emma (Tidsskrift for kulturforskning, 2008)
All but one of the contributions to this issue of Tidsskrift for kulturforskning originate from a seminar held on 7 December 2007 at the Department of Culture Studies and Oriental Languages, University of Oslo. The topic of the seminar was "Nature’s unnatural history", and its aim was to shed light on how shifting ideologies, moral standards and cultural patterns and conceptions have influenced human understandings of nature and science. Fortunately, the three speakers, Brian Ogilvie, Nigel Rothfels and Helge Kragh, all agreed to convert their oral presentations into articles, while Camilla Ruud has written the fourth article especially for this issue. To expand the perspectives that we find in the articles themselves, each is followed by a commentary.